2021
DOI: 10.1093/ejcts/ezab176
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve repair: outcomes after 17 years of experience

Abstract: OBJECTIVES This study presents the results of 17 years of experience with bicuspid aortic valve (BAV) repair and the analysis of factors associated with repair failure and early echocardiographic outcome. METHODS Between 2003 and 2020, a total of 206 patients [mean age: 44.5 ± 15.2 years; 152 males (74%)] with BAV insufficiency with or without aortic dilatation underwent elective aortic valve repair performed by a single surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Marek and colleagues, (7) in a study was to evaluate outcomes after 17 years of experience in repair of bicuspid aortic valve reported that 3% of patients were diabetic, 30% of patients were hypertensive, 5 % patients were smokers which confors with our preoperative parameters. The preoperative echo parameters (EF, ES and ED) were recorded for all our patients and revealed that mean EF 61.68±6.73%, ES 4.09±0.39cm and mean ED was 6.1±0.45cm.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Marek and colleagues, (7) in a study was to evaluate outcomes after 17 years of experience in repair of bicuspid aortic valve reported that 3% of patients were diabetic, 30% of patients were hypertensive, 5 % patients were smokers which confors with our preoperative parameters. The preoperative echo parameters (EF, ES and ED) were recorded for all our patients and revealed that mean EF 61.68±6.73%, ES 4.09±0.39cm and mean ED was 6.1±0.45cm.…”
Section: Discussionmentioning
confidence: 84%
“…The preoperative echo parameters (EF, ES and ED) were recorded for all our patients and revealed that mean EF 61.68±6.73%, ES 4.09±0.39cm and mean ED was 6.1±0.45cm. Similarly Jasinki and collegues, (5) in their study which was to evaluate a 17 year outcome after bicuspid aortic valve repair they revealed that preoperative mean EF 58.0±7.83%, ES 4.0±1.4cm and mean ED was 6.0±1.5cm. The cross clamp was also measured for all patients, the mean cross clamp time was 123.02±10.11minutes and bypass time was measured for all patients, the mean bypass time was 150.28±11.57minutes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, the Mayo group presented that the gradient can increase over time and may be responsible for late calcifications and stenosis. 3 Indeed, this failure pattern was noticed by authors in 25% of redo-operations in their paper. In very recent clinical data, it has been observed that proper annuloplasty is helpful in achieving better coaptation, especially for the asymmetric type BAV 1 or 2 or type 0 according to Sievers.…”
mentioning
confidence: 79%
“…The concept of durable annuloplasty ring could have an analogous effect in the case of a bicuspid aortic valve (BAV). Recently, the importance of circumferential annuloplasty in achieving durability of BAV repair has been proven, 6 and the BAV‐dedicated internal ring annuloplasty technology has been finally validated and applied clinically 7 . Inspired by the authors' excellent results in TAV, internal ring annuloplasty in BAV patients with additional replacement of nonfused sinus seems to be very promising.…”
mentioning
confidence: 99%